A mixed methods investigation into attitudes, behaviours, and health risk perceptions of Indonesian people regarding the use of kretek cigarettes - Nuryunarsih, Desy (2021)
Background Smoking is very common in Indonesia: among adults, around 66% of males and 7% of females are smokers. Smoking is not only harmful for people who smoke but also for people who are exposed to second-hand smoke on a regular basis. An estimated 90 million Indonesian people involuntarily inhale cigarette smoke every day. Every hour 46 Indonesians die due to smoking-related diseases. Globally, most smokers consume regular factory-made cigarettes, but in Indonesia, kretek (cigarettes with cloves and other additives) is the most popular tobacco product, smoked by around 90% of Indonesian smokers (54.2 million people). To date, no systematic review has investigated the health effects of kretek cigarettes. Research exploring Indonesian smokers and kretek has focused on the social and cultural aspects of smoking behaviour in Indonesia, and most of this is out of date. No research was found that specifically investigated the attitudes, knowledge, and health risk perceptions of the Indonesian population regarding kretek use. Health professionals (HPs) can play a key role in providing smokers with support to stop smoking, however, in Indonesia many HPs are reported to be smokers themselves. Data are needed to understand the smoking behaviours and attitudes of Indonesian HPs and their perceived role in helping smokers to stop.